THE IMPACT OF NEW MEDIA LITERACY AND SUPPLY CHAIN KNOWLEDGE MANAGEMENT ON COMMUNITY ECONOMY IN INDONESIA - Putri, K. Y.S; Adamu, Adamu Abbas; Mukhtar, Saparuddin; Safitri, Dini; Hafni, Rayni Delya; Fadhillah, Dini Nur (International Journal of Supply Chain Management, 2020)
This study aims to examine the impact of new media and supply chain knowledge management on community economy in Indonesia. This quantitative research method is distributed questionnaires to 157 respondents from retail sector in Indonesian. Based on dimensions of new media literacy, the strongest dimension is visualization with the highest average value of 3.40. Visualization enhances entrepreneur innovation in supply chain knowledge management. The results of this study indicate that new media literacy helps consumers on community economy in Indonesia.